Rapid determination of emerging contaminants in water and herbal infusions by in situ derivatization and gas chromatography-tandem mass spectrometry. Issue 7 (2nd March 2015) - Albero, Beatriz; Sánchez-Brunete, Consuelo; Miguel, Esther; Tadeo, José L.
Abstract : A simple and rapid method is proposed for the determination of fourteen emerging contaminants in water and different herbal infusions (tea, chamomile, linden-blossom and pennyroyal). Abstract : A simple and rapid method is proposed for the determination of fourteen emerging contaminants (ibuprofen, salicylic acid, fenoprofen, carbamazepine, diclofenac, hexestrol, dienestrol, diethylstilbestrol, estrone, mestranol, progesterone, 4-androstene-3, 17-dione, 17α-ethinylestradiol and propylparaben) in water and different herbal infusions (tea, chamomile, linden-blossom and pennyroyal). This procedure is based on the derivatization of the target analytes with ethyl chloroformate and ultrasound-assisted dispersive liquid–liquid microextraction with 100 μL of chloroform followed by gas chromatography-tandem mass spectrometry. The limits of detection of the target compounds ranged from 0.01 to 0.03 ng mL −1 in water and from 0.06 to 0.15 ng mL −1 in the different herbal infusions. The developed method was applied to water samples from different sources (well, river and dam) and herbal infusions and estrone was found in herbal infusions and five of the target compounds were detected in water at levels below 0.50 ng mL −1 .